Multi-criteria decision analysis of entrainers screening on the extractive distillation process for separating ternary mixtures based on multi-objective optimization - Xu, Zhixia; Wang, Yao; Li, Jinlong; Wu, Hanbin; Pan, Jing; Ye, Qing (Chemical engineering research & design, 2025)
This study aims to use multi-criteria decision analysis to investigate the impacts of relative volatility and the thermodynamic properties of entrainers on the extractive distillation process, using the separation of tetrahydrofuran/acetonitrile/water mixture as a case study. Based on the changes of relative volatility, four entrainers are chosen as candidate entrainers from eight widely used entrainers. A multi-objective algorithm is applied to optimize the extractive distillation processes of four entrainers. The optimization results indicate the economic, environmental, and entropy production advantages of the extractive distillation processes using four entrainers are ranked as follows: dimethyl sulfoxide> 1,2-propanediol>ethylene glycol> 1,3-propanediol. The multi-criteria decision analysis method based on entropy weight is adopted to evaluate the impacts of different influencing factors on the extractive distillation process. It indicates that alongside relative volatility, the impacts of the specific heat and boiling point of the entrainers on the extractive distillation process are significant and cannot be neglected. [Display omitted] •Multi-criteria decision analysis is applied to screen entrainers in ED.•The selection of entrainers takes into account thermodynamic properties.•NSGA-II algorithm is used to achieve the multi-objective optimization of process.•The specific heat and boiling point of the entrainers cannot be neglected in ED.